Aktivitas Antibakteri Ekstrak Rumput Laut Eucheuma cottoni terhadap Bakteri Escherichia coli, Staphylococcus aureus, Vibrio cholera dan Salmonella typhosa - Rizka Sartika; Melki .; Anna I.S. Purwiyanto (Maspari Journal : Marine Science Research, 2013)
Seaweed (Eucheuma cottonii) is one of the marine biological resources that contain flavonoid compounds as antibacterial agents. In a previous study the antibacterial Eucheuma cottonii, had been performed by dipping the disc paper into antibacterial extract, while in this study the antibacterial extract in exact volume will be dropped onto the disc paper, so we will know the volume certainty. The aims of the study were to determine the antibacterial activity and the minimum inhibitory concentration of the extract of Eucheuma cottonii test bacteria by using methanol solvent. The study was conducted in September-October 2012. In this study, seaweed extract made by using maceration method while the antibacterial activity testing by using agar diffusion method. The study results showed that the extract of Eucheuma cottonii antibacterial activity inhibited the growth of Staphylococcus aureus with inhibition zone diameter 17.33 mm, Escherichia coli with inhibition zone diameter 16,33 mm, Vibrio cholera with inhibition zone diameter 13,67 mm and Salmonella typhosa with inhibition zone diameter 11,67 mm. Minimum inhibitory concentration of Eucheuma cottonii to Escherichia coli, Staphylococcus aureus and Vibrio cholera were at 1% concentration while Salmonella typhosa was at 5 % concentration.Keywords: Antibacterial, Eucheuma cottonii, Minimum Inhibitory Concentration.